2000
DOI: 10.1038/sj.onc.1203759
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 activation of the GADD45 promoter

Abstract: Breast cancer susceptibility gene BRCA1 has been implicated in the control of gene regulation and such regulated genes are thought to mediate the biological role of BRCA1. Overexpression of BRCA1 induces GADD45, a p53-regulated and stress-inducible gene. However, the molecular mechanism by which BRCA1 induces the expression GADD45 remains unclear. In this report, we have shown that the GADD45 promoter is strongly activated following expression of wild-type BRCA1. In contrast, both the tumor-derived BRCA1 mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 31 publications
4
87
0
Order By: Relevance
“…But a partial deletion within exon 11 (Brca1 Dex11/Dex11 ) targeted to the mammary gland allowed survival with an increased incidence of breast cancer (Xu et al, 1999a) [see below]. BRCA1 causes transcriptional activation of the p21 WAF1/Cip1 and Gadd45 genes (Somasundaram et al, 1997;Harkin et al, 1999;Jin et al, 2000a), which contibute to proliferation inhibition and cell cycle blockade. Several studies, including our own, document a direct interaction between the BRCA1 and RB1 proteins, through two sites within BRCA1: (1) the carboxylterminal TAD (Yarden and Brody, 1998); and (2) an amino-terminal site within aa 300-400 (Aprelikova et al, 1999;Fan et al, 2001c).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
See 1 more Smart Citation
“…But a partial deletion within exon 11 (Brca1 Dex11/Dex11 ) targeted to the mammary gland allowed survival with an increased incidence of breast cancer (Xu et al, 1999a) [see below]. BRCA1 causes transcriptional activation of the p21 WAF1/Cip1 and Gadd45 genes (Somasundaram et al, 1997;Harkin et al, 1999;Jin et al, 2000a), which contibute to proliferation inhibition and cell cycle blockade. Several studies, including our own, document a direct interaction between the BRCA1 and RB1 proteins, through two sites within BRCA1: (1) the carboxylterminal TAD (Yarden and Brody, 1998); and (2) an amino-terminal site within aa 300-400 (Aprelikova et al, 1999;Fan et al, 2001c).…”
Section: Functional Activities Of Brca1 Cell Cycle Regulation and Gromentioning
confidence: 99%
“…Gadd45 is a DNA damage-responsive gene that occurs in three isoforms (a, b, and g) and functions in DNA repair, cell cycle checkpoint mechanisms, and apoptosis pathways (Kastan et al, 1992;Jin et al, 2000b;Sheikh et al, 2000;Tran et al, 2002). Several studies suggest that BRCA1 up-regulates the expression of Gadd45 (¼ Gadd45a), in part, by activating the Gadd45 promoter (Harkin et al, 1999;Jin et al, 2000a). BRCA1-mediated activation of the Gadd45 promoter occurred through association with Oct-1 and CAAT sites within the Gadd45 promoter and involved interactions between BRCA1 and the corresponding site-specific transcription factors, Oct-1 and NF-YA, respectively (Fan et al, 2002b).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%
“…The C-terminus of BRCA1, when fused to the GAL4 DNA binding domain activated GAL4 promoter. In transient transfection assays, BRCA1 increased p53-dependent and independent transcription from the p21 WAF1/CIP1 and GADD45 promoters (Chai et al, 1999;Jin et al, 2000). In addition, BRCA1 caused accumulation of p53 after gamma-irradiation through transcriptional stimulation of the p53-responsive promoter, MDM2.…”
Section: Introductionmentioning
confidence: 97%
“…Induction of apoptosis by the C-terminus of Brca1 occurs via GADD45/JNK pathway A study by Harkin et al (1999) showed that apoptotic initiation by full-length BRCA1 occurs via activation of the stress-responsive gene, GADD45. Further, in transient transactivation assays, BRCA1 activated the GADD45 promoter in a p53-independent manner (Jin et al, 2000;Thangaraju et al, 2000). Therefore, we examined if the pro-apoptotic activity of the Cterminus of BRCA1 relies, in part, on its ability to transactivate GADD45 in transient transfection assays utilizing CAT reporter under the control of GADD45 promoter (nt-994 to+1).…”
Section: Identification Of the Caspase-3 Cleavage Site In Brca1mentioning
confidence: 99%
“…These functions include regulation of centrosome duplication [1], acting as an E3 ubiquitin ligase [2], regulating cell cycle progression [3], repair of DNA damage [4] and serving as a transcriptional co-activator [5]. BRCA1 induces the expression of p21 Waf1/Cip1 [3] and GADD45 [6] genes, which encode proteins involved in cell *Corresponding author: Marilyn E. Thompson cycle control. This extant evidence is consistent with the interpretation that the ability of BRCA1 to regulate the cell cycle is based on its role as a transcription factor.…”
Section: Introductionmentioning
confidence: 99%